2019
DOI: 10.1371/journal.pone.0220058
|View full text |Cite
|
Sign up to set email alerts
|

Variability in phytoplankton biomass and effects of sea surface temperature based on satellite data from the Yellow Sea, China

Abstract: A time series of satellite data on Chlorophyll- a concentration (Chl- a ) that used ocean color was studied to determine mechanisms of phytoplankton variation in recent decade in the Yellow Sea, China during 2003–2015. The variability patterns on seasonal and inter-annual oscillation periods were confirmed using the Empirical Orthogonal Function (EOF), and Morlet wavelet transform analyses, respectively. The first EOF mode for Chl- a was domi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 46 publications
2
7
0
Order By: Relevance
“…From the linear trend analysis (obtained from MK test), an overall significant positive Chl-a trend was detected in the BYS during 2002-2018. This result is in agreement with previous studies, which also revealed positive Chl-a trends in the BYS or around its adjacent areas throughout similar periods (Kong et al, 2019;Liu et al, 2019;Xing et al, 2015;Zhang et al, 2017). The increased phytoplankton biomass in marginal seas was well documented and was likely related to enhanced coastal eutrophication (Boyce and Worm, 2015;Jickells, 1998;Marrari et al, 2016).…”
Section: Drivers For the Overall Positive Chl-a Trend In The Byssupporting
confidence: 92%
“…From the linear trend analysis (obtained from MK test), an overall significant positive Chl-a trend was detected in the BYS during 2002-2018. This result is in agreement with previous studies, which also revealed positive Chl-a trends in the BYS or around its adjacent areas throughout similar periods (Kong et al, 2019;Liu et al, 2019;Xing et al, 2015;Zhang et al, 2017). The increased phytoplankton biomass in marginal seas was well documented and was likely related to enhanced coastal eutrophication (Boyce and Worm, 2015;Jickells, 1998;Marrari et al, 2016).…”
Section: Drivers For the Overall Positive Chl-a Trend In The Byssupporting
confidence: 92%
“…Consistent with the importance of regional variability in the Eastern Bering Sea highlighted in this study, regional climate effects have been observed in dense temperate European and North American forests, with cooler forest-floor temperatures attenuating species' responses to global warming via increased shading during the growing season (De Frenne et al, 2013). Similarly, regional changes in water masses, sea surface temperature, the El Niño-Southern Oscillation (ENSO), and the seasonal Northern Atlantic Oscillation (NAO) have driven phytoplankton variation and bottom-up trophic cascades in marine ecosystems (Liu et al, 2019). However, many other constraints, including biotic mutualism, trophic competition (Araújo et al, 2011) and other abiotic anthropogenic effects, such as habitat destruction (Colorado-Zuluaga, 2015), also regulate the geographically interactive dependency between species.…”
Section: Discussionmentioning
confidence: 74%
“…This study area belongs to the Southern Yellow Sea (119-123 • E, 32-37 • N), a part of the Yellow Sea in China. The Southern Yellow Sea is a semi-enclosed shallow sea with an average depth of 44 m (Figure 1) [31,32], covering an area of 309,000 km 2 . Influenced by the Yellow Sea Warm Current (YSWC), the Yellow Sea Cold Water Mass (YSCWM), the coastal current of the Yellow Sea, and the diluted current of the Yangtze River, the Southern Yellow Sea has complex hydrographic conditions [33].…”
Section: Study Areamentioning
confidence: 99%